PRODUCTION AND CHARACTERIZATION OF LIQUID DETERGENTS FROM SOME AGRICULTURAL WASTE PRODUCTS (Nigerian Journal of Technology, 2015)
The aim of this work is to produce and characterized liquid detergents using potassium hydroxide obtained from waste of agricultural materials. The waste agricultural materials are cocoa pods, maize cobs and plantain peels. This was done by ashing these materials in a furnace at a temperature of 1050oC and dissolving the ash in de-ionized water to obtain the corresponding hydroxides. The metallic ions in their ashes were analyzed at different temperatures in order to study the effect of temperature on the yield of potassium ion by using atomic absorption spectrophotometer. The temperatures range is 450oC to 1050oC. The obtained results show that the metallic ions of the ash of these materials increase with increase in temperature. Analysis was carried out on the ashes of these materials to determine the oxide of elements in the samples ashed at 1050oC using X-ray fluorescence. The characteristics of the detergents formulated were carried out and compared with those of existing detergents purchased in market. The products were characterized based on the following parameters; percentages of active detergent, free oxide, total oxide, lather volume, phosphate, sodium tripolyphosphate, silica and silicate. Also, pH, viscosity and specific gravity. All the characterized properties of the detergents prepared and those purchased in the market fall within the standard for the detergent production. It was discover that the characteristics of the detergents prepared from waste agricultural materials are better than those detergents purchased in the market. http://dx.doi.org/10.4314/njt.v35i1.10